Evaluation of the Effect Coronavirus Lockdown had on Chronic Disease Management Care in Pediatrics: A Survey of Jordanian Pediatricians - Salma M. Burayzat; Muna Kilani; Redab Al-Ghawanmeh; Mohnad Odeh; Omar Assi; Karem H. Alzoubi (International Journal of Clinical Practice)
The outbreak of the COVID-19 pandemic puts a great strain on the healthcare system, as the national and global infection rates increased rapidly. Efforts were devoted to minimizing the effects of the spreading pandemic without overwhelming the already stretched healthcare system. The study objective was to establish how coronavirus lockdown was affecting chronic disease care among pediatric patients admitted to hospitals in developing countries. For that purpose, a cross-sectional survey of registered pediatricians was carried out. Findings showed that the mortality rate from COVID-19 in children seemed to be low. However, children with chronic illnesses were likely to be gravely affected by the disturbance of repetitive healthcare services. About 79% of pediatricians treated a child with a chronic condition during the lockdown. Furthermore, 15% of patients with chronic diseases visiting pediatricians exhibited uncontrolled emerging complications. In addition, 9% of pediatricians reported one to five fatalities among children under their care due to delay or lack of appropriate medical care in the period of the lockdown. Residents (48.9%) reported a significantly (p < 0.001) higher proportion of providing face-to-face services compared with consultants (17.9%) and specialists (13.6%). In conclusion, the care of chronically ill children should be taken into consideration when implementing lockdown and/or social distancing, thus minimizing the negative effects of lockdown and/or social distancing on children with chronic diseases.